Die Dramatisierung der Macht: Zur Genealogie von Foucaults Metapher der Werkzeugkiste - Stéphane Boutin (Genealogy+Critique, 2015)
This paper traces some genealogical lines of Foucault's famous tool-box metaphor by discussing hermeneutic and anti-hermeneutic analogies between theory and tool usage. Contrasting Deleuze's and Guattari's philosophy of asignifying machines with Heidegger's and Fink's phenomenological fascination for operativity, the article argues that Foucault's tool imagery draws heavily on Nietzsche's "philosophizing with a hammer". This genealogical hammer is read as a storytelling device used by Nietzsche and Foucault to dramatize historic conflict, staging power relations as complex plays of strategic instrumentality. The ongoing relevance of this dramatization tool is finally examined in David Simon's The Wire.